Support technology in sport psychology - career transition of elite athletes: role of mental training - Sasaba, I.; Sakuma, H. (Proceedings of the 3rd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2015)
Presently, various technologies are used more and more often in the field of sport psychology. This paper introduces two cases of how elite athletes use support technology in their mental training. One of the cases involves the use of Information Communication Technology (ICT), described in detail as qualitative research regarding elite athletes facing career transition. Becoming an Olympian dominates athletes` entire lives. Elite athletes` need for career transition support has recently become more recognized; therefore, international sports powerhouses tend to provide their own national support programs for elite athletes during their career transitions; for instance, the Japanese Olympic Committee began a career support program in 2004. In parallel with similar movements around the world, sport psychology consultants are often naturally called upon to address career transitions when working with elite athletes. The results show athletes` needs for career transition support and how sport psychology consultants can help these athletes as ultimate stage of their mental training. Possible interventions (approaches) are also presented.